MAINTENANCE COST TERJADWAL TINGKAT SEDANG PESAWAT GROB G 120 TP-A di SKADRON TEKNIK 043 ADISUTJIPTO YOGYAKARTA - Ginting, Charis Ira Sujana; Rahamawati, Fajar Khanif; Mulyani, Sri (Vortex, 2022)
The aircraft that used in this research is Grob G 120TP-A. Purpose of this research is support planning costs for scheduled maintenance in the period of 2020 and forecast the maintenance costs on the PI-600 flight hours for the period 2021, so that the aircraft is always in a state of airworthiness in order to support the implementation of operational activities as a training aircraft for the Indonesian Air Force. Maintenance costs on Periodic Inspection 600 flight hours of Grob G 120 TP-A aircraft in 2020 include employee salaries, spare parts, consumable materials, and fuel costs. Forecasting maintenance costs using the trend exponential method which uses maintenance cost data from 2016 to 2020. The results of the 600 flight hours of periodic inspection maintenance costs are Rp.476.527.879,92.and the results of forecasting maintenance costs for the Periodic Inspection 600 Flying Hours of the Grob G 120 TP-A aircraft using the trend least square method for the 2021 fiscal year is Rp. 408.667.919,9.